Surface properties of CuCl2/AC catalysts with various Cu contents: XRD, SEM, TG/DSC and CO-TPD analyses - Han, MS; Lee, BG; Ahn, BS; Moon, DJ; Hong, SI (ELSEVIER, 2003)
Surface properties of CuCl2/activated carbon (AC) catalyst for dimethyl carbonate synthesis were studied by CO-TPD, XRD, SEM and thermogravimetry (TG)/differential scanning calorimetry (DSC) with varying Cu contents. CUCl2/AC catalysts were prepared by impregnating AC with CUCl2-ethanol solution in the range of Cu content from 2.8 to 18.7 wt.%. CUCl(2)(.)2H(2)O crystalline phase as active sites was gradually increased with an increase in Cu content. Appearance of CUCl(2)(.)2H(2)O was clearly identified by XRD and SEM. In relatively low Cu contents, 4.6 and 9.9 wt.%, CUCl2.2H(2)O was not detected in XRD. This indicates the formation of good dispersion of CUCl2 compounds on activated carbon. However, DSC result revealed that CUCl(2)(.)2H(2)O was formed in multi-layers for the catalyst with Cu content more than 9.9 wt.%, which limit the catalyst activity. This fact was also strongly supported by CO-TPD experiment. The two CUCl2/AC catalysts having Cu contents of 4.6 and 9.9 wt.% showed no difference in CO adsorption amount in TPD experiments. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: ELECTRON-ENERGY-LOSS; OXIDATIVE CARBONYLATION; DIMETHYL CARBONATE; DESORPTION